Disrupted multi-scale topological organization of directed functional brain networks in patients with disorders of consciousness. Issue 2 (28th March 2023) - Guo, Yu; Cao, Bolin; He, Yanbin; Xie, Qiuyou; Liang, Qimei; Lan, Yue; Zhang, Mingxian; Qiu, Yidan; Yu, Ronghao; Huang, Ruiwang
Abstract: Disorders of consciousness are impaired states of consciousness caused by severe brain injuries. Previous resting-state functional magnetic resonance imaging studies have reported abnormal brain network properties at different topological scales in patients with disorders of consciousness by using graph theoretical analysis. However, it is still unclear how inter-regional directed propagation activities affect the topological organization of functional brain networks in patients with disorders of consciousness. To reveal the altered topological organization in patients with disorders of consciousness, we constructed whole-brain directed functional networks by combining functional connectivity analysis and time delay estimation. Then we performed graph theoretical analysis based on the directed functional brain networks at three topological scales, from the nodal scale, the resting-state network scale to the global scale. Finally, the canonical correlation analysis was used to determine the correlations between altered topological properties and clinical scores in patients with disorders of consciousness. At the nodal scale, we observed decreased in-degree and increased out-degree in the precuneus in patients with disorders of consciousness. At the resting-state network scale, the patients with disorders of consciousness showed reorganized motif patterns within the default mode network and between the default mode network and other resting-state networks. At the global scale, we found a lower global clustering coefficient in the patients with disorders of consciousness than in the controls. The results of the canonical correlation analysis showed that the abnormal degree and the disrupted motif were significantly correlated with the clinical scores of the patients with disorders of consciousness. Our findings showed that consciousness impairment can be revealed by abnormal directed connection patterns at multiple topological scales in the whole brain, and the disrupted directed connection patterns may serve as clinical biomarkers to assess the dysfunction of patients with disorders of consciousness. Abstract : Guo et al . reported the abnormal connection patterns based on directed functional brain networks at multiple topological scales and their correlations with clinical performances for the patients with disorders of consciousness. The findings suggested that directed interactions at multiple scales may exert a crucial role in the maintenance of consciousness. Graphical Abstract: Graphical abstract